Investigation on withdrawal capacity of staple in the upholstered furniture frame made of LVL - Mosayeb Dalvand; Ghanbar Ebrahimi; Kambiz Pourtahmasi (تحقیقات علوم چوب و کاغذ ایران, 2017)
In this study effect of staple length (penetration length) and its number in connection, on withdrawal capacity in face and edge of laminated veneer lumber (LVL) out of poplar was investigated. In this investigation, the staple with 3 and 4 cm penetration length and staple with 3, 4 and 5 cm penetration length for withdrawal capacity in face and edge were used respectively. Number of staples at 4 levels (2, 3, 4 and 5) were chosen as a variable. Results have shown that withdrawal capacity in face significantly increases with increase of penetration length. Withdrawal capacity in edge increases drastically with increase of penetration length from 3 to 4 cm, but increase in penetration length from 4 to 5 cm had no significant effect. Withdrawal strength capacity in face has increased with increase of staples number. But, increase of staple number had no significant effect on withdrawal strength capacity in edge. Maximum withdrawal capacity was observed in joints fabricated with penetration length of staple 4 cm and number of 5 staples in face and minimum those were observed with penetration length 3 cm and number of 2 staples in edge.